Long-term immunogenicity after yellow fever vaccination in immunosuppressed and healthy individuals. Issue 19 (23rd April 2020) - Burkhard, J.; Ciurea, A.; Gabay, C.; Hasler, P.; Müller, R.; Niedrig, M.; Fehr, J.; Villiger, P.; Visser, L.G.; de Visser, A.W.; Walker, U.A.; Hatz, C.; et al.
Abstract: Background: The live-attenuated yellow fever vaccine (YFV) is generally contraindicated in immunosuppressed patients. Our aim was to investigate if immunosuppressive therapy impairs the long-term protection against yellow fever virus in patients who had received YFV prior to the start of their immunosuppressive therapy. Methods: Our study examined 35 healthy individuals and 40 immunosuppressed patients with autoimmune diseases or organ transplants. All individuals had received YFV prior to the onset of their immunosuppression. We analysed the long-term influence of the immunosuppressive therapy on the YFV protective immunity by measuring neutralising antibodies (NA) with the Plaque Reduction Neutralisation Test (PRNT). We assessed risk factors for a negative PRNT result (titre below 1: 10) and their influence on the magnitude of the NA. Results: A median time interval of 21.1 years (interquartile range 14.4–31.3 years) after the YFV in all patients, a total of 35 immunosuppressed patients (88%) were seropositive (PRNT ≥ 1:10) compared to 31 patients (89%) in the control group. The geometric mean titres of NA did not differ between the groups. The duration of an underlying rheumatic disease was the only risk factor found for a lower magnitude of NA. An insufficient level of NA was found in nine subjects (12%) who had received a single dose of YFV (in one subject, the number of YFV doses was unknown). Conclusion: The use of an immunosuppressive drug started after the administration of the YFV did not affect long-term persistence of NA. A second dose of YFV may be necessary to secure long-term immunity.